The Relationship of Leadership with the Implementation of Patient Safety Culture in Hospitals - Fanny, Nabilatul; Amin, Nur Azma; Sari, Devi Pramita (Journal of Economics and Public Health, 2024)
Patient safety training at Hospital X has only been attended by a few people in hospital management. Every month around 3-10 incidents are reported. In the reporting, unexpected events were found. Target: nurses in inpatient and outpatient rooms totaling 120 people. Method: analytical survey with a cross-sectional approach. The independent variable is leadership, the dependent variable is the implementation of patient safety culture. The sampling technique is total sampling. Data analysis uses univariate and bivariate analysis. Results: The characteristics of respondents are mostly 23-30 years old, with more females than males (74.2%). The highest last education is S.Kep.,Ners (38.3%) and D3 (61.7%). The longest work period is 6-10 years (48.3%). Leadership is in the good category (90%). The implementation of patient safety culture in hospitals shows good results (86.7%). The results of the Spearman Rank test obtained a P-value of 0.000, meaning that there is a relationship between leadership and the implementation of patient safety culture in hospitals. Conclusion: There is a relationship between leadership and the implementation of patient safety culture. Suggestion, it is expected that the hospital can sort out efforts to improve patient safety culture appropriately.